Replicating "Run-off elections in the laboratory" - Carina I. Hausladen; Shiang-Hung Hu; Joel M. Levin (Institute for Replication (I4R), 2024)
Bouton et al. (2022) compare the properties of majority run-off and plurality rule elections in a laboratory setting, focusing on Duverger's prediction that plurality rule leads to higher levels of strategic voting. They produce a causal estimate of the difference in incidence of strategic voting across systems, finding more strategic voting under the plurality rule. However, they find that coordination is only higher under the plurality rule when voters are sufficiently divided over which candidate they prefer. They conclude that differences in electoral outcomes and voters' welfare are modest. We are able to computationally reproduce the original study's main findings using the authors' replication package. The replication package contained both raw data and a cleaned dataset, but did not include a script for cleaning the raw data or a codebook to make sense of it. Therefore, the majority of our work focused on producing code to evaluate and clean the authors' raw data. The authors sent a very helpful response to an earlier draft of this report and their communication improved the quality of our replication effort.
Keywords: C92; D70; 330; Majority run-off system; Plurality rule; Duverger's prediction; Voting behavior; Sincere voting